2013
DOI: 10.6001/zemesukiomokslai.v20i3.2739
|View full text |Cite
|
Sign up to set email alerts
|

Žemės ūkio paskirties žemės naudojimo tendencijos nenašių žemių savivaldybėse

Abstract: Straipsnyje nagrinėjama žemės ūkio veiklai naudojamų teritorijų raida nenašių žemių savivaldybėse. Atliekant tyrimus pasirinktos savivaldybės, kuriose vidutinis žemės našumas įvertintas mažiau nei 37 našumo balais (t. y. dirvožemių ūkinė vertė įvertinta tiek pat, kiek vertinami smėlio ir žvyro dirvožemiai arba nuardyti dirvožemiai). Iš 52 šalies kaimiškųjų savivaldybių mažiau nei 37 balais įvertintos 18 savivaldybių žemės. Be to, tokio našumo žemės yra ir 18 kitų savivaldybių, 48 seniūnijose. Tyrimui pasirinkt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(2 reference statements)
0
1
0
Order By: Relevance
“…Bykovienė et al (2014) estimated that in Lithuania, there are 23 municipal territories that have poor conditions for land use because of its rolling, hilly relief. Abalikštienė and Aleknavičius (2013), based on cartographic sources and recent statistical data, have identified that non-productive land is more abandoned and farming is less intensive than the regions prevailed by more productive land. Jarasiunas (2016) reported regionalisation of agricultural land for farming by steep slope criterion.…”
mentioning
confidence: 99%
“…Bykovienė et al (2014) estimated that in Lithuania, there are 23 municipal territories that have poor conditions for land use because of its rolling, hilly relief. Abalikštienė and Aleknavičius (2013), based on cartographic sources and recent statistical data, have identified that non-productive land is more abandoned and farming is less intensive than the regions prevailed by more productive land. Jarasiunas (2016) reported regionalisation of agricultural land for farming by steep slope criterion.…”
mentioning
confidence: 99%